DEVELOPING SPATIAL COMPETENCES IN GEOLOGY USING STEREOGRAPHIC PROJECTION - Carneiro, Celso Dal Ré; Miguel, Gisele Francelino (Boletim Paranaense de Geociências, 2025)
Undergraduate students of Geology must develop scholarship skills and attitudes that allow them to solve different types of geological problems encountered in real situations. The resolution of many problems involves geometric analysis, at different scales, of the structures of rock bodies, to characterize displacements and deformations. Stereographic projection techniques enable a geoscientist to represent, manipulate and associate three-dimensional structural data on a two-dimensional surface. Spatial thinking is important and indispensable in the geologist’s career; therefore, it is necessary to create opportunities for Geology students to acquire the required skills. This research developed workshops on stereographic projection techniques for undergraduate and graduate students, at the Geosciences Institute of the State University of Campinas, in order to facilitate the development of a 3D view and improve learning of Structural Geology topics. The manual (2D) and digital (2D-3D) stereographic resolution techniques were combined in the workshops, facilitating the understanding of the fundamental principles of each projection method, and their association with reference books on Structural Geology. The combination of 2D-3D techniques also facilitates the development of spatial cognition.